Black neo-Victoriana - Tronicke, Marlena 1987- (Brill, 2022)
"Black Neo-Victoriana is the first book-length study on contemporary re-imaginations of Blackness in the long nineteenth century. Located at the intersections of postcolonial studies, Black studies, and neo-Victorian criticism, this interdisciplinary collection engages with the global trend to reimagine and rewrite Black Victorian subjectivities that have been continually marginalised in both historical and cultural discourses. Contributions cover a range of media, from novels and drama to film, television and material culture, and draw upon cultural formations such as Black fandom, Black dandyism, or steamfunk. The book evidences how neo-Victorian studies benefits from reading re-imaginations of the long nineteenth century vis-à-vis Black epistemologies, which unhinge neo-Victorianism's dominant spatial and temporal axes and reroute them to conceive of the (neo-)Victorian through Blackness"
Includes bibliographical references and index
2111
Keywords: Geschichte 1837-1901; Geschichte 1970-2020; Kultur; Literatur; Englisch; Rezeption; Film; Schwarze; Großbritannien; Blacks / Great Britain / History / 19th century; Blacks / Social conditions / 19th century; Blacks / Race identity / History / 19th century; Blacks / Intellectual life / 19th century; Blacks in mass media; Blacks in literature; Great Britain / Civilization / 19th century